Soil quality in sustainable agricultural production systems - Borges, Wander Luis Barbosa; Sarto, Marcos Vinicius Mansano; de Souza, Isabela Malaquias Dalto [UNESP]; Juliano, Pedro Henrique Gatto [UNESP] (My University, 2021)
The adoption of sustainable agricultural production systems is important to increase/maintain the chemical, physical and biological fertility of the soil. Among these systems we have the no-tillage, agropastoral and agrosilvipastoral systems. To quantify changes in the chemical, physical and biological attributes of the soil under different sustainable agricultural production systems, three research projects were developed in the State of São Paulo, Brazil. The first project was developed at the Advanced Research Center for Rubber and Agroforestry Systems (CAPSSA) of the Agronomic Institute - IAC in an agrosilvipastoral system. The second project was also developed at CAPSSA in different production systems: no-tillage, agropastoral system, agrosilvipastoral system and conventional single pasture, comparing them to the condition of native forest (Cerrado). The third project was developed at Embrapa Pecuária Sudeste in different production systems: silvipastoral system, silviagricultural system and conventional single pasture, comparing them to the condition of native forest.
Keywords: Agro-pastoral system; Agrosilvipastoral system; No-tillage system; Soil attributes